Biomolecular therapeutics for human cancer - Giordano, Antonio; Macaluso, Marcella (Cancer epigenetics, 2011)
"Biomolecular Therapeutics for Human Cancer is the only resource to focus on biomolecular approaches to cancer therapy. Its presentation of the latest research in cancer biology reflects the interdisciplinary nature of the field and aims to facilitate collaboration between the basic, translational, and clinical sciences"--Provided by publisher.